Mild Haemostatic Problems Associated with Congenital Heterozygous α2-Antiplasmin Deficiency - Leebeek, F W G; Stibbe, J; Knot, E A R; Kluft, C; Gomes, M J; Beudeker, M (Thrombosis and Haemostasis, 1988)
A Dutch family, of which 13 members are heterozygotes, deficient for α2-antiplasmin (α2-AP) is reported. Clinical studies showed that 2 heterozygotes had a mild bleeding tendency, which presented as bleeding episodes after tooth extraction and after surgery and, in one patient, also as excessive menstruation. Laboratory investigations revealed an α2-AP activity of 62% (51-71) (median and range) and an antigen level of 60% (60-66). The plasminogen binding as well as the fibrin binding properties of α2-AP were normal. Plasminogen concentrations were significantly higher in the heterozygotes compared to the other family members. However, free plasminogen not bound to histidine-rich glycoprotein was not significantly different between these two groups. We propose that in this family the deficiency of α2-AP is due to a decreased synthesis of a normal α2-AP molecule. This present study brings the frequency of heterozygous α2-AP deficient patients with a bleeding tendency to 13 out of 59 heterozygotes reported in the literature.
Keywords: Fibrinolysis; α2-antiplasmin; Deficiency; Plasminogen; Haemorrhagic diathesis